Quality change of combined extrusion products during storage - Annenkova, Nadiya (КНТЕУ, 2006)
The results of quality changes research of new combined extrusion products, depending on receipt, packing and terms of storage are represented. The prolonged term of storage of these products is substantiated.
Keywords: quality; extrusion products; storage; качество; якість; екструдовані продукти; зберігання; кафедра експертизи харчових продуктів